The Protection of Animals under Malaysian and Islamic Law - Mohamad, Abdul Basir; Ismail, Nurbazla (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The topic of animal protection within the framework of Islamic law is receiving more and more attention in contemporary society. Even though the Quran and hadiths contain explicit verses highlighting the significance of protecting animal rights and welfare in connection to environmental conservation, numerous instances of animal abuse and cruelty continue to occur at all societal levels. According to a report published by the Department of Veterinary Services (DVS), there has been a significant rise in animal abuse instances in Malaysia. From 2021 to June 2024, 7,613 abuse complaints were received, with the biggest number occurring in Selangor. Dogs are the most mistreated animals, followed by cats and other creatures. This problem is not limited to animals. The ecosystem’s equilibrium, human-environment relations, and animal welfare are all impacted by this problem. Hence, the objective of this study is to analyse how Malaysian and Islamic law treat animal protection. This study’s methodology is qualitative and focuses on gathering data from a variety of primary and secondary sources, such as the Quran, hadith, books on Islamic jurisprudence, and scholarly sources like laws, books, articles, journals, and papers about animal protection and animal abuse cases. In the meantime, descriptive and comparative methods are used to analyse data. According to this study, Islam firmly condemns animal cruelty, as evidenced by numerous Quranic verses and the Prophet’s (peace be upon him) hadith that stress the value of animal welfare. Islam also mandates that people treat animals with compassion. In the meantime, the Animals Act 1953 (Revised 2006) (Act 647) and the Animal Welfare Act 2015 (Act 772) in Malaysia rigorously guard against any cruelty or damage to animal habitats. Animal abuse and cruelty must be condemned in order to preserve natural harmony and ecosystem equilibrium. The findings of this study have consequences for society in terms of protecting animals in line with Islamic laws and expectations.